Recent land issues and policies in the northern province: reconciling or reviving past demons? - Fonseka, B.; Raheem, M. (University of Jaffna, 2012)
Land has been a central issue in the post-independence history of Sri Lanka and as a result of discriminatory policies and practices is considered a root cause of the conflict. Land is intrinsically linked to a diverse range of other issues ranging from individual rights and basic needs to post-war reconstruction and development processes to collective identity and political autonomy. Policies and legislation on land and related issues have historically played a divisive role, particularly land distribution, resulting in colonisation schemes, massive development, changing ethnic demographics and with it resulting electoral change and impacting the larger political context. Challenges to administration, competing politico-military actors, loss of documentation coupled with a context of war and large-scale movement has created a complex situation on the ground in terms of confusion over and competing land claims. Although the end of the war provides an opportunity to address the root causes of conflict and introduce reform, there is limited evidence to demonstrate a paradigm shift or a genuine willingness by policy makers to address grievances. Instead, post war in Sri Lanka has witnessed a continuation of trends such centralisation, politicisation, militarisation and secrecy surrounding new policies, especially in relation to issues such as land. This study builds on research done by the authors on land issues in Sri Lanka, including the North but will look draw upon other work including historical, anthropological and political texts to examine the repercussions of this problem on reconciliation. In this study, the authors examine specific cases in the North including competing claims, military occupation and restrictions and state/political involvement in supporting ‘land grabs.’ It will also assess the socio-political impact on current government policies, mechanisms to address disputes and specific assistance programs, and how they exacerbate or ameliorate relations between communities. The inability of authorities to introduce a policy framework and provide solutions to address grievances can undermine reconciliation both at the national but also at the community level. The authors argue that recent debates and developments surrounding land issues in the North feeds into fears of the minority community of continued marginalisation, discrimination and dispossession.